Literature Review: Analisis Faktor Risiko Pneumonia pada Balita - Mukhammad Antonio Nuh Vicasco; Dwi Handayani (Universitas Nahdlatul Ulama Surabaya, 2020)
Pneumonia is acute respiratory infection affecting human lungs. Pneumonia is the one of caused high number of illness and death on toddler. Purpose of this literature review is to analyze pneumonia’s risk factors on toddler. This research is a literature review study. Main data course comes from multiple database that is Google Scholars, Garba Rujukan Digital and Proquest between 2015-2020. The keyword used is “pneumonia pada balita” dan “pneumonia on children under five years of age”. After screening, there is 12 relevant articles and became analysis materials for this research. The result is 6 of 12 journals explained a history of exclusive breastfeeding is a pneumonia risk factors on toddler, 5 of 12 journals explained nutritional status is pneumonia risk factors on toddler, 5 of 12 journals explained immunization status is pneumonia risk factors on toddler and 4 of 12 journals explained a history of low birth weight is pneumonia risk factors on toddler. Conclusion of this literature review is a history of exclusive breastfeeding, nutritional status, immunization status and a history of low birth weight are risk factors that influence the incidence of pneumonia on toddler. Therefore, for health workers is active to providing education about pneumonia’s risk factors that is the important of exclusive breastfeeding, increase immunization coverage, monitoring nutrition status by Health Card Toward (KMS) and increase antenatal care